2021
DOI: 10.1007/s11071-021-06659-x
|View full text |Cite
|
Sign up to set email alerts
|

Amplifying the response of a driven resonator via nonlinear interaction with a secondary resonator

Abstract: We study the dynamics of a resonantly driven nonlinear resonator (primary) that is nonlinearly coupled to a non-resonantly driven linear resonator (secondary) with a relatively short decay time. Due to its short relaxation time, the secondary resonator adiabatically tracks the primary resonator and modifies its response. Our model, which is motivated by experimental studies on the interaction between nano-and microresonators, is relatively simple and can be analyzed analytically and numerically to show that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Figure 1). Instead, these distributions shown in Figures 6(d, e), with additional resonators activated to a high-amplitude state, exist because of the interplay between the coupling and nonlinearity (Rosenberg and Shoshani 2021). Note that although the coupling parameters (α, β) are identical for each distribution, the Global Coupling Force G is distinct for each solution.…”
Section: Bifurcation Diagramsmentioning
confidence: 94%
“…Figure 1). Instead, these distributions shown in Figures 6(d, e), with additional resonators activated to a high-amplitude state, exist because of the interplay between the coupling and nonlinearity (Rosenberg and Shoshani 2021). Note that although the coupling parameters (α, β) are identical for each distribution, the Global Coupling Force G is distinct for each solution.…”
Section: Bifurcation Diagramsmentioning
confidence: 94%
“…Rosenberg et al. [ 513 ] analytically and numerically demonstrated that nonlinear interaction between two resonators with large difference in the relaxation times can significantly enhance the driven response of the slowly decaying (primary) resonator. They found that when the excitation frequency of the relatively fast decaying (secondary) resonator becomes near to the resonance frequency of the primary one, the linear coupling between the pair of driven resonators results in increasing the direct drive of the primary resonator.…”
Section: Fundamental Concepts Of Nano/micromechanical Resonatorsmentioning
confidence: 99%
“…Signal amplification of driven M/NEMS resonators, which can be performed by electrical [ 510,511 ] and mechanical [ 395,512,513 ] means, is crucial for achieving a large signal‐to‐noise ratio in engineering applications. Rosenberg et al.…”
Section: Fundamental Concepts Of Nano/micromechanical Resonatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the vibrations of micro-and nano-electromechanical resonators have provided a new realm of applications for nonlinear vibrations [1][2][3][4]. Many significant advances have been made in theory [5][6][7], experiments [8][9][10], and applications [11][12][13], including exploring new phenomena uncovered in previously unattainable parameter regimes [14][15][16]. The dynamics of these systems range from simple Duffing responses [17][18][19] to more exotic responses, sometimes involving two or more interacting vibration modes [20][21][22].…”
Section: Introductionmentioning
confidence: 99%